ddPCR Quantasoft Files for quantification of Atlantic salmon - Dumas Deconinck; Kris Hostens; Isabel Taverniers; Filip A.M. Volckaert; Johan Robbens; Sofie Derycke (Zenodo, 2021)
Quantasoft data used for the results section in the paper: "Identification and semi-quantification of Atlantic salmon in processed and mixed seafood products using Droplet Digital PCR (ddPCR)" Identification and semi-quantification of Atlantic salmon in processed and mixed seafood products using Droplet Digital PCR (ddPCR)